2004
DOI: 10.1016/j.neuropharm.2004.03.013
|View full text |Cite
|
Sign up to set email alerts
|

H1-receptor stimulation induces hyperalgesia through activation of the phospholipase C-PKC pathway

Abstract: The supraspinal cellular events involved in H 1 -mediated hyperalgesia were investigated in a condition of acute thermal pain by means of the mouse hot-plate test. I.c.v. administration of the phospholipase C (PLC) inhibitors U-73122 and neomycin antagonized the hyperalgesia induced by the selective H 1 agonist FMPH. By contrast, U-73343, an analogue of U-73122 used as negative control, was unable to modify the reduction of the pain threshold induced by FMPH. In mice undergoing treatment with LiCl, which impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…At present, biased signalling is proposed to be useful in several diseases, including heart failure (β-adrenergic receptors) [97][98][99] , hyperlipidaemia (nicotinic acid receptors) 100,101 , hypertension (α 2 -adrenergic receptors) 102 , some neuropsychiatric and/or neurodegenerative disorders (histamine H 1 receptors) 103 , hypothyroidism (thyroid-stimulating hormone receptor) 104 , small-cell lung cancer (gastrin-releasing peptide (GRP) and vasopressin receptors) 68 , schizophrenia (dopamine D 2 receptors) [105][106][107] , osteoporosis (PTH receptors) 67,108,109 , Parkinson's disease (dopamine D 1 receptors) 110 , diabetes (GLP1 receptors) 69 , as well as addiction, psychosis and depression (5-hydroxytryptamine (5-HT; serotonin) receptors) [111][112][113] .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…At present, biased signalling is proposed to be useful in several diseases, including heart failure (β-adrenergic receptors) [97][98][99] , hyperlipidaemia (nicotinic acid receptors) 100,101 , hypertension (α 2 -adrenergic receptors) 102 , some neuropsychiatric and/or neurodegenerative disorders (histamine H 1 receptors) 103 , hypothyroidism (thyroid-stimulating hormone receptor) 104 , small-cell lung cancer (gastrin-releasing peptide (GRP) and vasopressin receptors) 68 , schizophrenia (dopamine D 2 receptors) [105][106][107] , osteoporosis (PTH receptors) 67,108,109 , Parkinson's disease (dopamine D 1 receptors) 110 , diabetes (GLP1 receptors) 69 , as well as addiction, psychosis and depression (5-hydroxytryptamine (5-HT; serotonin) receptors) [111][112][113] .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Other interactions between T1AM signaling and histamine circuitry have been identified. Histamine has been demonstrated to modulate pain at the cortical and subcortical level, inducing hyperalgesia at low doses through H1 receptors (Malmberg-Aiello et al, 1994 ; Galeotti et al, 2004 ). In line with these observations, i.c.v.…”
Section: Neurological Effects Of T1ammentioning
confidence: 99%
“…In the former, histamine H 1 and H 2 receptors are involved in the modulation of pain sensations. [15][16][17] In the peripheral nervous system, it is reported that pyrilamine (histamine H 1 receptor antagonist) and cimetidine (histamine H 2 receptor antagonist) show analgesic effects in the formalin test. 18) In addition, anti-histaminic drugs show antinociceptive effects on formalin-induced stimuli.…”
Section: Discussionmentioning
confidence: 99%